Penerapan Clickbait Pada Judul Berita Kriminal Di Media Online Memorandum Sebagai Upaya Menarik Perhatian Pembaca (Studi Periode Januari Dan Februari 2026) - Cahya Fitra Sava Ardhiani; Julyanto Ekantoro; Tira Fitriawardhani (CV. ITTC INDONESIA, 2026)
The low literacy rate among the indonesia public means that some readers tend to focus only on news headlines without understanding the full content. This phenomenon has led the online media outlet Memorandum to use clickbait in its crime news headlines to attract readers attenton. Not all readers are able to distinguish between clickbait headlines and informative ones, which can lead to misunderstandings regarding the news content. This study aims to examine how clickbait is applied to crime news headlines on the online media Memorandum during the January and February 2026 period as an effort attract readers attention.This study employs a qualitative method with data collection techniques involving documentation and interviews. Documentation was conducted by classifying criminal news headlines on the online media platform Memorandum during the January and February 2026 period that contained clickbait elements, while interviews were conducted with representatives from Memorandum to gather information.The results of the authors research indicate that clickbait is employed in the headlines of crime news on the online media Memorandum through the use of sensational clickbait that tends to exaggerate. This is evident in the word choices used in the headlines of these crime news stories. This can evoke emotional reactions and curiosity in readers, thereby encouraging them to click on the presented headlines. Clickbait is consistently applied to the criminal news headlines created, while adhering to guidelines regarding content that does not contain elements of SARA issues or coercive bullying.